2021
DOI: 10.1186/s12978-021-01066-2
|View full text |Cite
|
Sign up to set email alerts
|

Causes of short birth interval (kunika) in Bauchi State, Nigeria: systematizing local knowledge with fuzzy cognitive mapping

Abstract: Background Short birth intervals, defined by the World Health Organization as less than 33 months, may damage the health and wellbeing of children, mothers, and their families. People in northern Nigeria recognise many adverse effects of short birth interval (kunika in the Hausa language) but it remains common. We used fuzzy cognitive mapping to systematize local knowledge of causes of kunika to inform the co-design of culturally safe strategies to address it. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previous work in Africa has shown that involving local perspectives can help to develop culturally respectful interventions for the promotion of reproductive health. 76 77 The literature map suggested that Western research has focused on understanding access to biomedical healthcare services as an outcome, as indicated by a higher indegree centrality in the map. Disrespect for Indigenous groups (cultural unsafety) and harsher material conditions accumulated to hinder Indigenous women’s access to Western services and affected other factors in the literature map.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in Africa has shown that involving local perspectives can help to develop culturally respectful interventions for the promotion of reproductive health. 76 77 The literature map suggested that Western research has focused on understanding access to biomedical healthcare services as an outcome, as indicated by a higher indegree centrality in the map. Disrespect for Indigenous groups (cultural unsafety) and harsher material conditions accumulated to hinder Indigenous women’s access to Western services and affected other factors in the literature map.…”
Section: Discussionmentioning
confidence: 99%
“…Causes of adverse ASRH outcomes identified on the maps will inform the contextualization of the survey instruments. Based on our experience of FCM of causes of short birth interval in Bauchi, we expect they will include causes at individual, family, community, and service levels [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…We will prepare summarized outputs from the transitive closure analysis of the cognitive maps [ 29 ]. With support from the research team, groups of approximately 15 adolescent girls and boys respectively, identified through a local NGO, the Federation of Muslim Women’s Associations in Nigeria (FOMWAN), will produce materials to share evidence from the maps and baseline survey, including short video docudramas in the style of popular local soap operas.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations